Pengaruh Profitabilitas, Kebijakan Deviden Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018- 2020 - Ni Kadek Ayu Sintya Devi; Kadek Dewi Padnyawati (UNHI Press, 2023)
In making a decision to invest funds, investors will certainly pay attention to the number of dividends that will be distributed to them. The value of the company is a fundamental consideration for investors to choose the company that they will invest in. A good company value will certainly convince investors that the company has good performance. This study was conducted to analyze several factors that can affect the value of a manufacturing company. The data of this research is obtained from secondary data sources where the population is 195 manufacturing companies that are officially listed on the IDX. The research sample amounted to 132 financial statements and analyzed by regression technique. This study found that firm value can be influenced by increasing profitability, increasing number of dividend policies, and capital structure that can be arranged optimally.